2021
DOI: 10.1177/2329048x211012544
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Barriers to Adherence With Neurology Clinic Appointments for Children With Epilepsy: A Pilot Study

Abstract: Introduction: Epilepsy is one of the most common neurological disorders in children. Missed appointments reflect missed opportunity to provide care for children with epilepsy. The objective of this study was to identify social determinants of health (SDH) and other factors associated with missed appointments in children with epilepsy and measure the relation between missed appointments and frequency of emergency room (ER) visits and inpatient admissions. Methods: This was a prospective study conducted in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…19,20 Many factors including economic and logistic factors, mistrust in the health care system, and systemic racism have been attributed to these differences. 10,14,2830 In our study, audio visits reduced the odds of missed appointments for all children; this association was more pronounced for children of Black race. Similar moderating effect was not seen with video visits.…”
Section: Discussionsupporting
confidence: 43%
“…19,20 Many factors including economic and logistic factors, mistrust in the health care system, and systemic racism have been attributed to these differences. 10,14,2830 In our study, audio visits reduced the odds of missed appointments for all children; this association was more pronounced for children of Black race. Similar moderating effect was not seen with video visits.…”
Section: Discussionsupporting
confidence: 43%
“…They also demonstrated a link between missed appointments and increased emergency department visits related to seizures. 7 However, they did not utilize predictive analytics to prospectively determine the likelihood of missing a scheduled appointment. The factors around insurance status deserve more attention to determine specific barriers that lead to missed patient appointments.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent study reported that children with epilepsy who had a higher number of previous no-shows to a pediatric neurology clinic visit had a higher frequency of emergency department visits and a 6 times higher likelihood of inpatient hospitalizations related to seizures. 7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonattendance leads to higher health care costs and further decreases access to subspecialty care, while potentially compromising patient safety. [13][14][15][16] Numerous studies have evaluated referral communication processes between PCPs and subspecialists as well as appropriate reasons for referral. [17][18][19][20] But less is known about why patients fail to complete subspecialty referrals, particularly in pediatrics.…”
Section: Introductionmentioning
confidence: 99%